Simulating underactuated multibody dynamics using servo constraints and variational integrators - Leitz, Thomas; Leyendecker, Sigrid (Proc. Appl. Math. Mech. (PAMM), 2014)
In underactuated dynamical systems, the number of control inputs nu is smaller than the number of degrees of freedom nq. Real world examples include e.g. flexible robot arms or cranes. In these two exmples the goal is to prescribe the trajectory of an end effector and find the necessary control variables. One approach to model these problems is to introduce servo constraints in the equations of motion that enforce a given trajectory for some part of the syste